Turismo sustentável, alternativa de desenvolvimento local e conservação ambiental. uma análise interdisciplinar do PRODETUR - Ce - Lima, Josael Jario Santos (2003)
The tourism model conceived and incentivated, for the last eleven eyers, by the government of the state of Ceará (Northeast Brazil), has grounded on the context of a globalized economy, and its characteristcs, resemblance those of the Mexican and Caribbean models, by means of social exclusion, elitism, public space privatization, cultural homogenization, production of not-place without community life or identity ties. Such a model tends to create and to maintain a private appropriation of publics spaces, like beaches and water springs, to accent the desigualitys of income and one region poor, and desprovid of ivestiments the implementation of infra-sruture, a long time in that operate by midle bulky publics expense whitout consulte the society and integrating the interest and need of the greater number of populaion . The present invetigation had the objetive basic the sistemic and sistemattic knowledge in perspective transdisciplinar, the condicions in that went concept e implemented the Tourism Development Program in Northeast of Brazil (PRODETUR-NE) and of Ceará (PRODETURCE), in area prioritary for alacation of investiments public and private in the Region Turistic II on the State of Ceará. A field survey among the social actors in the of Cumbuco/Lagoa do Barro (Caucaia), Pecém (São Gonçalo do Amarante), Paracuru, Lagoinha (Paraipaba), Flecheiras (Trairi) e Baleia (Itapipoca) tried tried to capture their perceptions about real improvements in the population quality of life, through more and better job, wages and income, increased environmental preservacion/conservacion, and stronger cultural assertion, according to the new paradigm of developement sustentable. Next, an attempt was made in order to correlate offcial statistic data with the percepcion captured by above mentione participative and semi-strutured field survey. The results show a fucional and strutural system of turism, with a weak sustainably in the long run, for not ensuring and efetive improvement of the majority of the local population quality of life, for reinforcing negative environmental impacts, socio-space segregacion, cultural the descharacterization, generation and increase of some social problems like infant-juvenile prostitution and drugs traffic, at the same time that tourism job expectations frustrate young people mostly. From all that, restructuring of strategies and priorities is recommended, in order to attain the genuine Local-Integrated- Sustainable Development (LISD), through people’s participation and decentralization of management which empowers local communities.